2022
DOI: 10.1128/spectrum.00459-22
|View full text |Cite
|
Sign up to set email alerts
|

Goblet Cell Hyperplasia Increases SARS-CoV-2 Infection in Chronic Obstructive Pulmonary Disease

Abstract: SARS-CoV-2 or COVID-19’s first case was discovered in December 2019 in Wuhan, China, and by March 2020 it was declared a pandemic by the WHO. It has been shown that various underlying conditions can increase the chance of having severe COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 102 publications
1
29
0
Order By: Relevance
“…However, we found that the IS4 "NSPR" created a pat7 NLS "PRRARSV" in the S protein, which was unique to SARS-CoV-2. We first reported that the S protein translocated into the nucleus in the SARS-CoV-2-infected airway epithelium, which is an appropriate lung model for studying respiratory virus infection in vitro [2,43]. Our results confirmed that the SARS-CoV-2 S protein was a unique addition to the list of viral proteins that possess NLSs and consequently translocate into the nucleus of infected cells [17,30,31,44].…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…However, we found that the IS4 "NSPR" created a pat7 NLS "PRRARSV" in the S protein, which was unique to SARS-CoV-2. We first reported that the S protein translocated into the nucleus in the SARS-CoV-2-infected airway epithelium, which is an appropriate lung model for studying respiratory virus infection in vitro [2,43]. Our results confirmed that the SARS-CoV-2 S protein was a unique addition to the list of viral proteins that possess NLSs and consequently translocate into the nucleus of infected cells [17,30,31,44].…”
Section: Discussionsupporting
confidence: 72%
“…In this study, we used cells from five donors: nonsmoker healthy adults (donors #1 and #2) and adult with chronic obstructive pulmonary disease (COPD) (donor #3). The protocols for subculturing primary NHBE cells were published previously [2, 43, 50]. SARS-CoV-2 (USA/WA-CDC-WA1/2020 isolate, GenBank accession no.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations